Crescimento de nanofios auto-sustentados de arseneto de índio por epitaxia por feixes moleculares - Rodrigo Ribeiro de Andrade (2010)
This Thesis reports the experimental and theoretical works related to the growth and characterization of free-standing gallium indium arsenide nanowires grown by Molecular Beam Epitaxy (MBE). The growth mechanisms of free-standing nanowires remain barely known and explored in its fundamental aspects. The theoretical models of the formation of free-standing nanowires are based on the classical vapor-solid-liquid (VLS) mechanism suggested by Wagner and Ellis in the 1960 decade or on the surface diffusion of precursors adatoms towards the nanowire top, developed in the last decade by several authors.In this study, gallium indium arsenide nanowires were grown by Molecular Beam Epitaxy (MBE) on GaAs (111)B substrates coated with Au nanoparticles catalytic. This Au nanoparticles has an average diameter of 5nm. The Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) were use to characterize morphology, chemical composition and crystalline structure of individual nanowires. We use thediffraction of X-rays in coplanar and grazing incidence geometry (GID Grazing Incidence Diffraction) to analyze a large nanowires set. The anomalous diffraction of Xrays analysis complemented these studies.Our results show that the nanowires has a cubic symmetry like spharelite (zinc blende) oriented along [111]B in the shape of hexagonal bars surrounded by six vertical {110} facets. Chemical composition analysis shows that they were composed of the indium, gallium and arsenic elements, all homogeneously distributed along the nanowire. The presence of Ga in the chemical composition of the nanowire was surprising because only indium and arsenide were used as precursors during the growth. The MBE Ga source remained cold and locked during the nanowire growth. Our results has been found that a strong interdiffusion of substrate material occurs during growth, creating a ternary In(1-x)GaxAs alloy in the nanowires. The GaAs molar fraction was found to increase with the growth temperature and decreases with the As4 beam. This ternary alloy has been attributed to the interdiffusion of Ga adatoms coming from the top substrate monolayers and diffusing towards the sidewalls to nanowires. To explain these results we developed a complementary growth model of free-standing nanowires to include the creation and diffusion of Ga adatoms from the substrate, well explaining the formation of the ternary alloy. This work shows that the diffusion of substrate adatoms strongly modifies the growth mechanisms of nanofios grown by vapor phase epitaxy techniques.